Biotesting of Chlorella sp algae for certain medicinal drugs - Zadagali, А.М.; Zhamangara, А.K. (Fundamental and Experimental Biology, 2022)
In recent years, the study of drugs as pollutants in the country is gaining momentum. This is because the country does not use special wastewater treatment devices for pharmaceuticals. They enter the environment in different ways. Therefore, research on biotesting drugs in living organisms is underway. The article presents the results of experiments conducted to assess the effect of paracetamol, azithromycin, suprastin on the num-ber and biomass of Chlorella sp algae. Chlorella sp algae are a widely used organism for biotesting. Among the above drugs in the study, paracetamol had a negative effect on the number and biomass of algae. The minimum harmful concentration of paracetamol for chlorella was 5 mg/L, the minimum harmful concentra-tion of azithromycin for chlorella was 200 mg/L, the minimum harmful concentration of chlorella suprastin was 8 mg/L. When comparing the effect of paracetamol, azithromycin, suprastin on the number of green algae Chlorella sp, it was observed that paracetamol had the highest effect. Concentration of paracetamol 10mg/L brought the number of chlorella close to 0. High concentrations of paracetamol and suprastin in the biomass of chlorella showed contamination of the environment.